Experimental investigation of performance and emission characteristics of a miniature gas turbine supplied by blends of kerosene and waste tyre pyrolysis oil. (15th January 2021) - Suchocki, T.; Witanowski, Ł.; Lampart, P.; Kazimierski, P.; Januszewicz, K.; Gawron, B.
Abstract: Fossil fuels are non-renewable sources of energy that could be depleted in the near future, giving rise to a major energy crisis. Scientists from all over the world are working on new technologies to produce fuel not only from renewable sources but also from waste. This article is concerned with: (i) waste tyre management by means of the pyrolysis process, (ii) investigation of physico-chemical parameters of waste tyre pyrolysis oil (TPO), and (iii) investigation of performance and emission characteristics of a miniature GTM-140 turbine engine supplied by blends of kerosene and waste tyre pyrolysis oil. The final aim of the research is to determine the influence of the applied blend composition (between 10 and 50% of TPO in the blends) on the performance and emission parameters of a small gas turbine. Turbine inlet and outlet temperatures, fuel flow, static thrust, thrust specific fuel consumption (TSFC) and emissions index of NOx, CO, SO2 are measured in a wide range of turbine load. The differences are the largest for the highest rotational speeds, where the temperatures, TSFC and emissions of NOx especially tend to increase with the increasing fraction of pyrolytic oil in the blends, as compared to those of kerosene. However, emissions of SO2 are lower for the all blends in the entire range of load. Highlights: Waste tyre management by means of the pyrolysis process is described. Physico-chemical properties of waste tyre pyrolysis oil are investigated. Gas turbine supplied by blends of JET A and tyre pyrolysis oil is investigated. Slightly higher values of thrust specific NOx and CO emissions are observed.